Striving for Business Success : Voices of Liberian Women Entrepreneurs - World Bank Institute (Washington, DC, 2014)
Women in post-conflict economies face a number of challenges. Often their businesses stay at embryonic stages only, due to three key limitations relating to: knowledge of business vision and management; access to finance and markets; and access to role models and networks. Added to the complexity is the risk of having to start all over again due to their countriesapos; political instability and the limited infrastructure to make their businesses proper and become more efficient over time. This report presents findings on the situation of women entrepreneurs in Liberia. It discusses the challenges that female entrepreneurs face as well as enabling factors that they encounter when operating their businesses in Liberiaapos;s post-conflict environment. Through the voices and experiences of women - as in the IFC series quot;Voices of Women Entrepreneursquot; that inspires it - this report sheds some light on the specificities of women doing business in fragile and conflict-affected situations (FCS), such as those in Liberia. It identifies operational lessons and proposes recommendations on how to support women entrepreneurs and contribute to their economic empowerment in the transition from post-conflict to reconstruction and development. The women interviewed for this report highlighted how obstacles, such as limited financial infrastructure, restricted access to markets, and most importantly, insufficient networks to support women entrepreneurs, stifle efforts to create sustainable solutions for women entrepreneurs. The report offers operational lessons and recommendations on how to address these challenges and support womenapos;s economic participation and empowerment.